1994
DOI: 10.1111/j.1365-2125.1994.tb04338.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of pharmacokinetic interaction between vinpocetine and oxazepam.

Abstract: The influence of multiple doses of vinpocetine (10 mg three times daily) on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Up to the present, several publications have reported the interactions of vinpocetine with other clinical prescription drugs. According to Storm et al [ 16 ], multiple doses of vinpocetine showed no influence on the steady state plasma concentrations and kinetics of oxazepam but cause diurnal changes in the plasma binding of oxazepam without clinical consequences. The values of AUC 0− t , AUC 0−inf , and C max following the single administration of vinpocetine alone and after pretreatment of 5 days with omeprazole (10 mg/kg, intraperitoneally) were very similar in both groups [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to the present, several publications have reported the interactions of vinpocetine with other clinical prescription drugs. According to Storm et al [ 16 ], multiple doses of vinpocetine showed no influence on the steady state plasma concentrations and kinetics of oxazepam but cause diurnal changes in the plasma binding of oxazepam without clinical consequences. The values of AUC 0− t , AUC 0−inf , and C max following the single administration of vinpocetine alone and after pretreatment of 5 days with omeprazole (10 mg/kg, intraperitoneally) were very similar in both groups [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic interactions arise when absorption, distribution, metabolism, or elimination of the involved drugs is altered, leading to changes in the amount and duration of drug availability at receptor sites. More precisely, the most common DDI of pharmacokinetics may be understood in terms of metabolic alterations, primarily associated with changes in the activity of cytochrome P450 (CYP) enzymes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation